Competitiveness and Wage Bargaining Reform in Italy - Kangur, Alvar (Washington, D.C. : International Monetary Fund, 2018)
The growth of Italian exports has lagged that of euro area peers. Against the backdrop of unit labor costs that have risen faster than those in euro area peers, this paper examines whether there is a competitiveness challenge in Italy and evaluates the framework of wage bargaining. Wages are set at the sectoral level and extended nationally. However, they do not respond well to firm-specific productivity, regional disparities, or skill mismatches. Nominally rigid wages have also implied adjustment through lower profits and employment. Wage developments explain about 45 percent of the manufacturing unit labor cost gap with Germany. In a search-and-match DSGE model of the Italian labor market, this paper finds substantial gains from moving from sectoral- to firm-level wage setting of at least 3.5 percentage points lower unemployment (or higher employment) rate and a notable improvement in Italy's competitiveness over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet